Santa Cruz 1991: Represi Militer Indonesia di Timor Timur pada Era Orde Baru - Naziya, Ifsa (PT Inovasi Penelitian Terpadu, 2025)
This article aims to analyze the face of Indonesian military repression during the New Order era through the events of Indonesia's annexation of East Timor in 1975 and the Santa Cruz Tragedy in 1991. The research method adopts historical methods through the stages of heuristics (source collection), source criticism, interpretation, and historiography (historical writing). The annexation of East Timor created tensions between the Indonesian government and the East Timorese people, who wanted independence. The Santa Cruz Tragedy marked a turning point in Timor-Leste's independence struggle, demonstrating the Indonesian military's brutality against civilians who were peacefully demonstrating. Although Indonesia attempted to cover the event, the Santa Cruz Tragedy and media footage paved the way for Timor-Leste's independence on May 20, 2002. This event also underscored the importance of protecting human rights and the role of the media in uncovering the truth, and served as an important lesson for preventing similar violations in the future.